Development and Optimization of Polyethersulfone-Zeolite Mix Matrix Membrane Using Rice Husk Ash for Cadmium Removal in Landfill Leachate - Riana, Ulfa; Saiful*, Saiful; Ramli, Muliadi; Rashidi Abdull Manap, Mohd; Umam, Rofiqul (Universitas Syiah Kuala, 2025)
Increasing the volume of waste at the final disposal site will contribute to environmental pollution due to the seepage of leachate resulting from the waste decomposition process. Leachate is dangerous and toxic because it contains bacteria, organics or inorganic compounds, and heavy metals like cadmium (Cd). Therefore, methods for reducing Cd levels continue to be developed using a mixed matrix membrane. This research used the silica content from rice husk ash as a precursor for zeolite synthesis. The zeolite is then used as a filler to make politersufon-zeolite mixed matrix membrane (PES-zeolite MMM), which is applied to reduce Cd levels in leachate. The synthesized zeolite is a white solid that is similar to Na-A zeolite. The resulting PES-zeolite MMM showed better mechanical properties than the pure PES membrane. MMM has a tensile strength of 20.31 kgf/mm2, elongation of 105.5%, degree of expansion of 33.89%, porosity of 22.85%, and flux of 118.52 L/m2 hours. The optimum performance of PES-zeolite MMM in adsorption of Cd ions was obtained at a loading percentage of 40% and 30 minutes is the best contact period. The adsorption capacity of Cd ions is 2.27 mg/g. The adsorption isotherm model follows the Langmuir isotherm model with a correlation coefficient (R2) of 0.9152 and Qm of 3.35 mg/g. PES-zeolite MMM 40% can be regenerated using NaCl and HCl solutions, with the maximum adsorption capacity for each solution being 1.99 mg/g and 1.75 mg/g. Applying PES-zeolite MMM in leachate samples reduced Cd and Hg ions levels and several other leachate parameters